Electron Transport Materials: π‐Extended Spiro Core‐Based Nonfullerene Electron‐Transporting Material for High‐Performance Perovskite Solar Cells (Adv. Funct. Mater. 25/2020). (18th June 2020) - Hu, Zhao; Tang, Guanqi; Miao, Jingsheng; Fu, Tianchen; Li, Tingting; Tai, Qidong; Meng, Hong; Yan, Feng
Abstract : In article number 2001073, Hong Meng, Feng Yan, and co‐workers design, synthesize, and successfully use a non‐fullerene electron transport material based on a new spiro derivative, SPS‐4F, in perovskite solar cells, leading to high efficiency as well as good stability of the devices. This work opens a new avenue for developing new spiro‐based electron transport materials and paves a way for realizing high‐performance devices at low costs.